Analysis of solid blends milling using population balances (2019)
Particle size distribution (PSD) is a key factor in size reduction processes. These processes are widely used worldwide and in the Colombian industry. However, they represent a high energy consumption process, which requires a careful assessment of the desired particle size and the energy required to obtain it. In order to reduce the capital costs, it is common for some companies to operate grinding stages with blends, reducing the capital costs and time required for the process. However, the blend composition can affect the operating conditions or require a higher energy consumption than grinding the individual components. Population balance modeling (PBM) can be used to describe the rate at which a material is being ground, and therefore, predict the time and energy required to obtain a desired PSD. In this work, the grinding behavior of two different materials and their blend in a batch size reduction process using a laboratory-scale steel ball mill was studied. The operating conditions were kept constant in order to study the evolution of PSD with time. The results obtained showed a good correlation between PSD and time using PBM for the pure materials. The blend could not be explained by a linear combination of the parameters. Further work is necessary to study blends in milling processes. It was also possible to determine the effect of grinding media size and mill filling in the rate of breakage of solids. However, the applicability of the model was only adequate for the coarser sizes of the samples, as shown by validation experiments.